Method for the production of beryllium oxide ceramic structures
Patent Information
- Application Number
- CN202611312945.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]为克服现有的大型氧化铍陶瓷烧结易开裂、内外密度分布不均、晶粒尺寸大、热导率不达标的问题,本发明提供一种用于氧化铍陶瓷结构件的制备方法
通过喷雾造粒、级配振动填粉、冷等静压成型及预烧结+热等静压烧结(HIP)两步烧结,喷雾造粒改善粉体形貌、粉体级配、振动填料提高生坯均匀性、粉体抽真空排除夹杂气体,预烧+HIP两步烧结实现内外高密度均匀化与细晶强化的全流程制备方法,系统提升了氧化铍大型结构件的性能与成品率。
Smart Images

Figure CN123003263A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic preparation technology, and specifically to a method for preparing beryllium oxide ceramic structural parts. Background Technology
[0002] Beryllium oxide (BeO) ceramics possess excellent properties such as high thermal conductivity (theoretical value of about 310 W / (m·K)), low dielectric constant, high insulation, and a coefficient of thermal expansion that matches that of semiconductor materials, making them an irreplaceable material in fields such as spacecraft heat sinks and nuclear reactor components.
[0003] With the increasing demands on the size of ceramic structural components in the aforementioned fields, large beryllium oxide structural components are prone to problems such as sintering cracking, uneven internal and external density, insufficient core density, abnormal grain growth, and insufficient thermal conductivity. Therefore, it is of great significance to develop a method for preparing large beryllium oxide ceramic structural components with high density, fine grains, and high strength to improve thermal conductivity, strength, and product size. Summary of the Invention
[0004] To overcome the problems of easy cracking during sintering of existing large-scale beryllium oxide ceramics, uneven internal and external density distribution, large grain size, and substandard thermal conductivity, this invention provides a method for preparing beryllium oxide ceramic structural components.
[0005] The technical solution adopted by this invention to solve its technical problem is: A method for preparing beryllium oxide ceramic structural components includes the following steps: Step 1, Powder pretreatment: High-purity beryllium oxide powder is calcined and roughened, then sintering aid, binder and solvent are added and ball milled to obtain a slurry; the slurry is spray granulated to obtain granulated powder with an angle of repose ≤30°; Step 2, molding: After sieving the granulated powder obtained in Step 1, the powder is graded into coarse and fine particles, and then loaded into the mold by vibration filling. Vacuum is drawn to remove the gas between the powder particles, and then cold isostatic pressing is used to form a beryllium oxide ceramic green body. Finally, aging treatment is carried out to release stress. Step 3, Atmospheric pressure pre-sintering: The green blank obtained in step 2 is pre-sintered at a temperature not exceeding 1700℃. Step 4, hot isostatic pressing densification sintering and annealing: The sintered blank obtained in step 3 is subjected to hot isostatic pressing sintering in an inert gas atmosphere. The sintering temperature is not higher than the pre-sintering temperature in step 3. Then, it is annealed in an air atmosphere.
[0006] This invention employs a two-step sintering process involving spray granulation, graded vibration filling, cold isostatic pressing, and pre-sintering followed by hot isostatic pressing (HIP). Spray granulation improves powder morphology and gradation, vibration filling enhances green uniformity, and vacuuming removes inclusions. The two-step pre-sintering and HIP process achieves high internal and external density homogenization and fine grain strengthening, thus systematically improving the performance and yield of large beryllium oxide structural components.
[0007] In some embodiments, the high-purity beryllium oxide powder in step one has a purity of ≥99.5% and an average particle size of 200nm-400nm; the calcination and coarsening are carried out in a tunnel kiln at a sintering temperature of 1500℃-1600℃, and the particle size of the coarsened powder is 700nm-800nm.
[0008] In some embodiments, the ball milling medium in step one is deionized water, the grinding balls are beryllium oxide balls, and the particle size D50 of the slurry after ball milling is 1μm-1.2μm.
[0009] In some embodiments, the sintering aid in step one is magnesium trisilicate; the binder is polyvinyl alcohol; the solvent further includes plasticizer, glycerol, defoamer, dispersant, and oleic acid; and the slurry solid content is 58%-62%.
[0010] In some embodiments, the sieving in step two uses 40-mesh, 60-mesh, 80-mesh, or 100-mesh sieves, with a fine powder gradation ratio of 20%-40%; the mold is a polyurethane mold with a Shore A hardness of 70-90.
[0011] In some embodiments, the vibration frequency of the vibration filling in step two is 20Hz-80Hz, the amplitude is 0.5mm-2mm, and the vibration continues during the filling process; the vacuum degree of the vacuuming is 0.04MPa-0.06MPa, and the vacuuming time is 6h-12h.
[0012] In some embodiments, the cold isostatic pressing in step two employs a stepped pressurization and stepped depressurization method.
[0013] In some embodiments, the temperature regime for the segmented heating sintering in step three is as follows: heating to 80℃-100℃ at 0.3℃ / min-0.5℃ / min and holding for a period of time; heating to 600℃-800℃ at 0.2℃ / min-0.3℃ / min and holding for a period of time; heating to 1100℃-1200℃ at 0.15℃ / min-0.2℃ / min and holding for a period of time; heating to 140℃ at 0.12℃ / min-0.15℃ / min and holding for a period of time. Hold at 0℃-1500℃ for a period of time; raise the temperature to 1650℃-1700℃ at 0.1℃ / min-0.12℃ / min and hold for a period of time; lower the temperature: raise the temperature to 1300℃-1400℃ at 0.1℃ / min-0.15℃ / min, raise the temperature to 1100℃-1200℃ at 0.15℃ / min-0.3℃ / min and hold for a period of time, raise the temperature to 600℃-800℃ at 0.3℃ / min-0.5℃ / min and hold for a period of time before cooling down with the furnace.
[0014] In some embodiments, the process parameters for hot isostatic pressing sintering in step four are as follows: heating rate 4℃ / min-6℃ / min to 600℃-800℃, holding at that temperature for a period of time; heating rate 3.5℃ / min-4℃ / min to 1000℃-1100℃; heating rate 3℃ / min-3.5℃ / min to 1300℃-1350℃; heating rate 2℃ / min-3℃ / min to 1400℃-1450℃; heating rate 1℃ / min-2℃ / min to 1550℃-1650℃, holding at that temperature and pressure for a period of time; the pressure reaches 150 MPa before reaching 1550℃. The pressure is maintained at 200 MPa until the heat treatment is completed; the cooling rate is 1℃ / min-2℃ / min to 1450℃-1500℃, 2℃ / min-2.5℃ / min to 1200℃-1300℃, 2.5℃ / min-3℃ / min to 800℃-1000℃, 3℃ / min-4℃ / min to 300℃-400℃, and then cooled with the furnace; the gas introduced is Ar with a purity ≥99.99%; the annealing temperature in step four is 1200℃-1400℃, and the heating and cooling rate is 2℃ / min-4℃ / min.
[0015] In some embodiments, the pre-sintering arrangement method in step three is as follows: hollow spheres, shrinkage plates, hollow spheres, and beryllium oxide ceramic blanks are placed sequentially on the firing plate; the hollow spheres are alumina spheres with a diameter of 2mm-3mm, and the shrinkage plates are alumina green blanks.
[0016] The beneficial effects of this invention are: By employing a two-step sintering process involving spray granulation, graded vibration filling, cold isostatic pressing, and pre-sintering + hot isostatic pressing (HIP), the entire process of beryllium oxide large structural components is achieved. Spray granulation improves powder morphology and gradation, vibration filling enhances green uniformity, and vacuuming removes inclusions. The pre-sintering + HIP two-step sintering process achieves high internal and external density homogenization and fine grain strengthening, thus systematically improving the performance and yield of beryllium oxide large structural components.
[0017] Powder pretreatment and molding stage: Spray granulation obtains powder with high sphericity and good flowability (angle of repose ≤30°), and combined with coarse and fine powder gradation and vibration filling, significantly improves the bulk density and uniformity of green body; vacuuming removes gas, and stepped cold isostatic pressing and aging treatment effectively release internal stress and avoid cracking of large parts during molding.
[0018] Sintering stage: Pre-sintering at atmospheric pressure establishes a microstructure dominated by closed pores, creating the preconditions for HIP; HIP (1500℃-1700℃, 150MPa-200MPa) completely eliminates closed pores, achieving highly uniform internal and external density (0.5% density difference), and the temperature does not exceed the pre-sintering temperature. Combined with magnesium trisilicate additives to pin grain boundaries, fine-grained high-strength ceramics are obtained. Annealing further removes color centers and defects.
[0019] Overall effect: Effectively solves problems such as sintering cracking, uneven internal and external density, insufficient core density, and abnormal grain growth in large beryllium oxide ceramics, achieving an internal and external density difference ≤0.5% and high density (≥2.85g / cm³). 3 It has an average grain size of 3μm-10μm, high thermal conductivity (≥270W / (m·K)) and high flexural strength (≥190MPa), and has good industrial feasibility. It is suitable for nuclear reactor moderators, spacecraft heat sinks and load-bearing insulation structural components of nuclear fusion devices. Attached Figure Description
[0020] Figure 1 This is a process flow diagram of the method for preparing beryllium oxide ceramic structural parts provided by the present invention; Figure 2 This is a SEM image of the spherical powder obtained by spray granulation in Example 1 of the present invention; Figure 3 This is a schematic diagram of the blank placement process during pre-sintering in Embodiment 1 of the present invention; Figure 4 This is a schematic diagram of the blank placement process during pre-sintering in some other embodiments of the present invention; Figure 5 SEM comparison images of traditional sintering and the present invention; Figure 6 This is a schematic diagram of the density test sampling in Example 1.
[0021] The figures are labeled as follows: 1-sample, 2-hollow sphere, 3-alumina green, 4-sintering plate, 5-zirconia sphere. Detailed Implementation
[0022] The invention will be further described below with reference to the accompanying drawings.
[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0024] like Figure 1-6 As shown, the present invention provides a method for preparing beryllium oxide ceramic structural parts.
[0025] The preparation method for beryllium oxide ceramic structural parts refers to... Figure 1 As shown, it includes the following steps: Step 1, Powder pretreatment: High-purity beryllium oxide powder is calcined and roughened, then sintering aid, binder and solvent are added and ball milled to obtain a slurry; the slurry is spray granulated to obtain granulated powder with high sphericity and good flowability (angle of repose ≤30°).
[0026] Specifically, the process involves powder coarsening followed by spray granulation to improve morphology: First, high-purity beryllium oxide powder is placed in a sagger and calcined in a tunnel kiln for coarsening. Then, the coarsened high-purity beryllium oxide powder is used as raw material, with the addition of sintering aids, binders, dispersants, and other solvents, followed by ball milling until the particle size meets the requirements. Finally, the qualified ball-milled slurry is transferred to a spray granulation tower, and the appropriate parameters are set for spray granulation to obtain powder with high sphericity and good flowability.
[0027] Step 2, molding: The granulated powder obtained in Step 1 is sieved and then graded into coarse and fine powders. It is then loaded into the mold by vibration filling, vacuum is drawn to remove gas from the gaps between the powders, and then cold isostatic pressing is used to form a beryllium oxide ceramic green body. Finally, it is aged to release stress.
[0028] Specifically, the process involves powder gradation, vibratory filling, vacuuming, and cold isostatic pressing: First, the granulated powder is sieved through screens of different mesh sizes to achieve gradation. While excessively fine powder has high sintering activity, it is prone to cracking during sintering, while excessively coarse powder has insufficient sintering performance. Then, the mold is placed on a vibrating table, and the graded powder is gradually added while vibrating, allowing the particles to rearrange under vibration to achieve maximum packing density until the mold is full. Next, a vacuum pump is connected to the external port of the mold to evacuate the internal gases. After vacuuming, the mold filled with powder is sealed and placed in a cold isostatic pressing (COP) system. Appropriate parameters are set, and step-by-step pressure increase and depressurization are used to form the beryllium oxide ceramic green body. This prevents excessive compression leading to insufficient product rigidity and excessively rapid pressure release resulting in insufficient stress release and cracking. Finally, the green body is placed in a designated environment for stress release treatment.
[0029] Step 3, atmospheric pressure pre-sintering: The green blank obtained in step 2 is arranged accordingly to create an environment that maximizes shrinkage assistance, and a ceramic green blank with fewer open pores and more closed pores is obtained at a relatively low temperature (not higher than 1700℃).
[0030] The atmospheric pressure pre-sintering structure establishes closed pores and achieves a certain strength. Specifically, this involves: first, the large beryllium oxide structural components are arranged in a box furnace, with a firing support plate 4 placed at the bottom, followed by hollow spheres 2, then a shrinkage plate, and finally another hollow sphere 2. This provides an aid to facilitate smooth shrinkage during ceramic sintering. Then, an appropriate sintering regime is set, with segmented heating and sintering processes to provide sufficient heat transfer to the ceramic and ensure stability and uniformity during sintering. The cooling rate also needs to be controlled at a slow rate to prevent cracking. Finally, the pre-sintering stage can be carried out at a relatively low temperature, with the key goal of obtaining a ceramic blank with a certain density, few open pores, and many closed pores.
[0031] Step 4, Hot Isostatic Pressing (HIP) Densification Sintering and Annealing: The green body obtained in Step 3 is subjected to hot isostatic pressing sintering in an inert gas atmosphere. The sintering temperature is not higher than the pre-sintering temperature in Step 3. Then, it is annealed in an air atmosphere to obtain a large beryllium oxide ceramic structural part with uniform internal and external density, fine grains, high density and high thermal conductivity.
[0032] Hot isostatic pressing (HIP) densification sintering achieves uniform internal and external density and grain refinement. Specifically, it involves: first, placing pre-fired beryllium oxide ceramic into a mold within a HIP furnace, introducing inert gas, and gradually increasing temperature and pressure. Applying isotropic pressure at high temperature completely removes residual closed pores from the pre-fired ceramic due to plastic deformation and diffusion creep. The sintering temperature does not exceed the pre-sintering temperature, thus preventing grain regrowth. The high pressure effectively compresses the closed pores, resulting in reduced porosity and increased density. Before HIP, it is crucial to ensure a sufficiently small number of open pores within the ceramic; otherwise, the high pressure will penetrate the ceramic, failing to compact it and potentially damaging the internal structure. Finally, the HIP-treated beryllium oxide ceramic is annealed in air to eliminate impurities and contaminants introduced during the HIP process, effectively removing internal color centers and defects to optimize its performance.
[0033] The pre-sintering temperature should not exceed 1700℃, but it cannot be too low either. Too low a temperature will result in low density and numerous interconnected pores. This will prevent the creation of an internal and external pressure difference during HIP (Hyper-Insulation) sintering, thus hindering the compression of these pores and failing to achieve the intended HIP effect (HIP, for ceramics, primarily involves compressing and closing closed pores). The initial pre-sintering density should be between 90% and 95%. Conventional beryllium oxide ceramics require temperatures above 1700℃ to achieve the national standard density of 2.85. For pre-sintered products requiring HIP, temperatures can be set at 1600℃, 1650℃, or 1680℃, not exceeding 1700℃. Initially, the pores are mostly open pores; with gradual diffusion creep, most open pores disappear, leaving some closed pores. This is also related to the sintering temperature.
[0034] This invention employs a two-step sintering process involving spray granulation, graded vibration filling, cold isostatic pressing, and pre-sintering followed by hot isostatic pressing (HIP). Spray granulation improves powder morphology and gradation, vibration filling enhances green uniformity, and vacuuming removes inclusions. The two-step pre-sintering and HIP process achieves high internal and external density homogenization and fine grain strengthening, thus systematically improving the performance and yield of large beryllium oxide structural components.
[0035] Furthermore, the high-purity beryllium oxide powder mentioned in step one has a purity of ≥99.5% and an average particle size of 200nm-400nm; the calcination and coarsening are carried out in a tunnel kiln at a sintering temperature of 1500℃-1600℃, and the particle size of the coarsened powder is 700nm-800nm.
[0036] Furthermore, in step one, the ball milling medium is deionized water, and the grinding balls are changed from traditional zirconium oxide and alumina balls to special beryllium oxide balls, which effectively reduces the possibility of introducing impurities. The ball milling speed is 180 r / min, the ball milling time is 18h-24h, and the particle size D50 of the slurry after ball milling is 1μm-1.2μm.
[0037] Furthermore, the sintering aid mentioned in step one is magnesium trisilicate, with an addition amount of 0.5wt.%-1wt.% of beryllium oxide powder. Compared with conventional single MgO and SiO2 aids, the advantage of this aid is the synergistic effect of "liquid phase + solid phase" and more uniform mixing. It has the dual advantages of reducing sintering temperature and refining grains. Moreover, because the two are released simultaneously, the synergistic effect is better. The high-temperature decomposition releases the SiO2 component, generating a low-melting-point liquid phase in situ to promote densification; at the same time, the released MgO component pins the grain boundaries in situ, inhibiting excessive grain growth. Furthermore, the binder is polyvinyl alcohol (PVA); the addition amount is 1wt.%-2wt.% of the beryllium oxide powder, which enhances the particle adhesion and mechanical strength, improves flowability, promotes particle molding, and reduces the risk of molding cracking by coating the powder particles.
[0038] Furthermore, the solvents added in step one include, but are not limited to, plasticizer DOP, glycerol, added at a rate of 1 wt.%-2 wt.% of beryllium oxide powder; defoamer (n-octanol), added at a rate of 2 wt.%-3 wt.% of beryllium oxide powder; dispersant SD-00, added at a rate of 1.5 wt.%-2 wt.% of beryllium oxide powder; oleic acid, added at a rate of 0.2 wt.%-0.5 wt.% of beryllium oxide powder, etc.; this step requires obtaining a slurry with a solid content of 58%-62%.
[0039] Furthermore, the parameters for spray granulation in step one are as follows: the nozzle uses a spray plate with a nozzle diameter of φ0.3mm-φ0.5mm, the inlet temperature is 190℃-250℃, the outlet temperature is 100℃-130℃, the negative pressure inside the tower is maintained at 100Pa-300Pa, and the feed pump pressure is 1.2MPa-1.5MPa; the angle of repose of the resulting granulated powder is ≤30°, and the D50 is 100μm-120μm.
[0040] Furthermore, the sieving in step two uses 40-mesh, 60-mesh, 80-mesh, or 100-mesh sieves, with the fine powder gradation ratio being 20%-40%.
[0041] In actual research and development and production, different particle sizes of powder are involved. Coarse particles are defined as those with a mesh size of 60 mesh or less, and fine particles are defined as those with a mesh size of 80 mesh or more.
[0042] Furthermore, the mold is a polyurethane mold with a Shore A hardness of 70-90. Ceramic green bodies obtained from molds of this material and hardness have smooth surfaces and clear edges.
[0043] Furthermore, the vibration frequency of the vibratory powder filling device described in step two is 20Hz-80Hz, and the amplitude is 0.5mm-2mm, with continuous vibration during the powder filling process.
[0044] Furthermore, in step two, when evacuating the mold, the outer end interface of the mold must be perfectly connected to the vacuum pump interface (with the clamp tightly locked). The powder and the interface must be isolated with filter cloth to prevent the powder from being extracted. Turn on the vacuum pump and evacuate to a vacuum level of 0.04MPa-0.06MPa, maintaining the evacuation time for 6-12 hours.
[0045] Furthermore, the cold isostatic pressing in step two adopts a stepped pressure increase and stepped pressure decrease method: the pressure increase rate is 1MPa / s-2MPa / s, and the pressure is held for 1 minute at 20MPa, 50MPa, 100MPa, 125MPa, and 150MPa respectively, and then held for 5-8 minutes after increasing to 160MPa-180MPa; the pressure decrease rate is 1MPa / s-2MPa / s, and the pressure is held for 30 seconds at 145MPa, 130MPa, 105MPa, 55MPa, and 25MPa respectively, and then the pressure is released.
[0046] Furthermore, the aging process described in step two is as follows: first, place the raw blank in a clean environment with a temperature of 20℃-30℃, humidity of 50%-70%, closed environment without strong convection and pollution, and let it stand for 18h-24h. Then, put it in an oven and heat it to 25℃-75℃ at a rate of 1.5h / 10℃-2h / 10℃, and bake it for 18h-24h.
[0047] Furthermore, Figure 3 and Figure 4 Two methods of arranging the blanks are shown.
[0048] like Figure 3 As shown, the pre-sintering arrangement in step three is as follows: Hollow spheres 2, a shrinkage plate, another hollow sphere 2, and a beryllium oxide ceramic green body (sample 1) are placed sequentially on the firing plate 4. The hollow spheres 2 are alumina spheres with a diameter of 2mm-3mm and a complete, full shell shape. The shrinkage plate is an alumina green body 3. The overall arrangement environment must be level, and the hollow spheres 2 must be in uniform contact with sample 1.
[0049] like Figure 4 As shown, the pre-sintering arrangement method in step three is as follows: after placing zirconia balls 5 on the sintering plate 4, sample 1 is placed.
[0050] In comparison, Figure 3The blanking method shown eliminates shrinkage resistance to a greater extent, making it more suitable for the large, crack-prone structural components mentioned in this application.
[0051] Furthermore, the temperature regime for the segmented heating sintering in step three is as follows: heating at 0.3℃ / min-0.5℃ / min to 80℃-100℃, holding for 2 hours; heating at 0.2℃ / min-0.3℃ / min to 600℃-800℃, holding for 1 hour; heating at 0.15℃ / min-0.2℃ / min to 1100℃-1200℃, holding for 2 hours; heating at 0.12℃ / min-0.15℃ / min to 1400℃. ℃-1500℃, hold for 2 hours; heat up to 1650℃-1700℃ at 0.1℃ / min-0.12℃ / min, hold for 4 hours; cooling down: heat up to 1300℃-1400℃ at 0.1℃ / min-0.15℃ / min, heat up to 1100℃-1200℃ at 0.15℃ / min-0.3℃ / min, hold for 1 hour, heat up to 600℃-800℃ at 0.3℃ / min-0.5℃ / min, hold for 1 hour, and then cool down with the furnace.
[0052] Furthermore, the process parameters for hot isostatic pressing sintering in step four are as follows: heating rate 4℃ / min-6℃ / min to 600℃-800℃, holding for 1 hour; heating rate 3.5℃ / min-4℃ / min to 1000℃-1100℃; heating rate 3℃ / min-3.5℃ / min to 1300℃-1350℃; heating rate 2℃ / min-3℃ / min to 1400℃-1450℃; heating rate 1℃ / min-2℃ / min to 1550℃-16... The furnace is held at 50℃ for 2-4 hours; the pressure reaches 150MPa-200MPa before reaching 1550℃ and is maintained until the end of the holding period; the cooling rate is 1℃ / min-2℃ / min to 1450℃-1500℃, 2℃ / min-2.5℃ / min to 1200℃-1300℃, 2.5℃ / min-3℃ / min to 800℃-1000℃, and 3℃ / min-4℃ / min to 300℃-400℃, after which it is cooled with the furnace. Taking 1550℃ and 180MPa as an example, the pressure increases with the temperature, requiring the required 180MPa to be reached before 1550℃ and maintained until the end of the holding period; the pressure decreases as the temperature decreases.
[0053] Furthermore, in step four, the interior of the hot isostatic pressing furnace cavity is φ610mm*1000mm, and the gas introduced is Ar with a purity ≥99.99%.
[0054] Furthermore, the annealing temperature in step four is 1200℃-1400℃, the heating and cooling rate is 2℃ / min-4℃ / min, and the holding time is 3h.
[0055] The beryllium oxide ceramic large structural component has a dimension ≥15mm in at least one dimension and an overall density ≥2.85g / cm³. 3 With an internal and external density difference of ≤0.5%, an average grain size of 3μm-10μm, a room temperature thermal conductivity of ≥270W / (m·K), and a flexural strength of ≥190MPa, it can be used as a moderator in nuclear reactors, a heat sink for spacecraft, or a load-bearing insulating structural component for nuclear fusion devices.
[0056] Example 1: Preparation of BeO moderator for a nuclear reactor (dimensions: 260×280×60mm) (1) Powder pretreatment: Beryllium oxide raw material powder was calcined and coarsened in a tunnel kiln at 1550℃. The particle size of the coarsened powder was about 750nm. The coarsened powder was mixed with 0.8wt.% magnesium trisilicate, 1.2wt.% PVA, 1.0wt.% plasticizer DOP, 1wt.% dispersant SD-00, 0.35wt.% oleic acid, and 2.2wt.% defoamer n-octanol, etc., and ball-milled for 18 hours with deionized water as the medium. The particle size of the slurry was about 1.1μm. Spray granulation: the inlet temperature was 195℃ and the outlet temperature was 105℃. The resulting granulated powder had a D50 of 100μm and an angle of repose of 28°. The granulated powder was sieved through 40, 60, 80, and 100 mesh screens and then graded with a coarse-to-fine ratio of 7:3.
[0057] Reference Figure 2 As shown in the figure, the SEM image of the spherical powder obtained by spray granulation shows that the granulated powder has a high degree of sphericity, and the common "steamed bun" and "donut" shapes are basically absent. This greatly improves the flowability of the powder, which is more favorable for the rearrangement and initial density of subsequent shaped particles. For sintering, it can also greatly enhance the sintering driving force.
[0058] (2) Vibration molding and vacuuming: Place the polyurethane mold on the vibration table, and fill it while vibrating until the mold is full. Then connect the pipe and vacuum to 0.04 MPa. The vibration frequency is 50 Hz and the amplitude is 1 mm. Then cold isostatic pressing (CIP) is performed at a pressure of 160 MPa for 5 min. The relative density of the green body is 60%, and the maximum difference in density between the inside and outside of the same green body is 0.8%.
[0059] (3) Sintering: Pre-firing: Heat to 80℃ at 0.4℃ / min and hold for 2 hours; heat to 600℃ at 0.3℃ / min and hold for 1 hour; heat to 1200℃ at 0.2℃ / min and hold for 2 hours; heat to 1400℃ at 0.15℃ / min and hold for 2 hours; heat to 1680℃ at 0.12℃ / min and hold for 4 hours; cool to 1400℃ at 0.15℃ / min, cool to 1200℃ at 0.25℃ / min and hold for 1 hour; cool to 800℃ at 0.35℃ / min and hold for 1 hour, then cool down with the furnace. After pre-firing: Surface density 2.8154 g / cm³3 The transition zone concentration was 2.8013 g / cm³. 3 Core size 2.7854 g / cm 3 .
[0060] HIP sintering: Heat to 800℃ at 4.5℃ / min and hold for 1 hour; heat to 1100℃ at 4℃ / min; heat to 1300℃ at 3.5℃ / min; heat to 1500℃ at 2℃ / min; heat to 1650℃ at 1℃ / min and hold for 3 hours; cool to 1500℃ at 1.5℃ / min; cool to 1300℃ at 2.5℃ / min; cool to 1000℃ at 3℃ / min; cool to 400℃ at 4℃ / min and then cool with the furnace. Pressure increases with temperature, reaching the required 180MPa before reaching 1550℃ and holding until the end of the holding period. Pressure decreases as temperature decreases. The atmosphere introduced is ≥99.99%Ar.
[0061] (4) Annealing: air atmosphere, 1200℃, heating and cooling rate is 3℃ / min, hold for 3h.
[0062] Overall performance: The sintered beryllium oxide ceramic was intact, and no cracks were found after the interior was cut open. Overall density: 2.85 g / cm³ 3 -2.87g / cm 3 (Archimedes' method of drainage); Density uniformity: Surface layer 2.8631 g / cm³ 3 Transition layer 2.8595 g / cm 3 Core size 2.8587 g / cm³ 3 The maximum density difference is 0.17%.
[0063] Reference Figure 6 As shown, a vertical plane was cut, and 10*10*10mm cubic blocks were taken from the surface layer, transition layer, and core for testing. For sintered green bodies of conventional beryllium oxide ceramic large structural components, due to the problem of internal and external temperature difference transmission, the density of the exterior is generally greater than that of the interior. However, HIP (High-Intensity Intermediate Phosphate) can effectively reduce this density difference. Figure 6 The sampling method demonstrates the principle of sampling from the inside out and from top to bottom. This better reflects and proves the view that the density of beryllium oxide ceramics tends to be uniform after HIP.
[0064] Microstructure: Samples were prepared using SEM. The overall structure was clear, with no obvious pores, well-defined grain boundaries, uniform grains, and no abnormal grain growth observed. The average grain size was approximately 4.8 μm. (Reference) Figure 5 As shown, according to national standards, the grain size of beryllium oxide ceramics is generally required to be ≤20μm. Figure 5 Conventional beryllium oxide ceramics produced by traditional sintering typically have grains of around 20 μm, with numerous voids and irregular grain shapes. However, beryllium oxide ceramics produced using HIP (High-Intensity Interchange) can reduce grain size to 3 μm-5 μm, resulting in finer grains and fewer pores compared to traditional processes.
[0065] Thermal conductivity at room temperature: 282 W / (m·K) (laser flare method) The high-temperature thermal conductivity is shown in the table below:
[0066] Flexural strength: 195 MPa Example 2: Fabrication of a BeO high-power heat sink for a spacecraft (size: 300×200×15mm) (1) Powder pretreatment: Beryllium oxide raw material powder (purity ≥99.5%, average particle size 250nm) was calcined and coarsened in a tunnel kiln at 1500℃, and the particle size after coarsening was about 700nm. The coarsened powder + 0.5% magnesium trisilicate (to reduce the amount of liquid phase and reduce the thermal resistance of the grain boundary phase) + 1.0wt.% PVA + 2wt.% plasticizer DOP and glycerol + 2wt.% dispersant SD-00 + 0.3wt.% oleic acid + 2.3wt.% defoamer n-octanol, with deionized water as the medium and beryllium oxide balls as the grinding balls, was ball-milled for 20 hours, and the slurry particle size D50≈1.0μm. Spray granulation: the inlet temperature was 225℃, the outlet temperature was 115℃, the negative pressure in the tower was maintained at 150Pa, and the pump pressure was about 1.3MPa. The resulting granulated powder D50=105μm and the angle of repose was 26°. After sieving the granulated powder through 40, 60, 80, and 100 mesh sieves, a coarse-to-fine powder ratio of 7:3 is adopted.
[0067] (2) Vibration molding + vacuuming: The polyurethane mold (Shore A 80) is placed on a vibration table with a vibration frequency of 60Hz and an amplitude of 0.8mm. Powder is filled while vibrating. An external vacuum pump is used to evacuate to 0.05MPa and maintained for 8 hours to ensure that the gas between the powder particles is fully removed.
[0068] Cold isostatic pressing: stepwise pressurization (rate 1.5 MPa / s) to 180 MPa (hold pressure for 1 min at 20 MPa / 50 MPa / 100 MPa / 125 MPa / 150 MPa, and hold pressure for 6 min at 180 MPa). Step-by-step pressure relief (rate 1.5 MPa / s, holding pressure at 145 MPa / 130 MPa / 105 MPa / 55 MPa / 25 MPa for 30 seconds each).
[0069] The relative density of the green body is 61%, and the maximum density difference between the inside and outside of the same green body is 0.7%. Aging treatment: 25℃, 60% humidity, stand for 24 hours, then bake at 75℃ for 20 hours at a rate of 1.5h / 10℃.
[0070] (3) Sintering: Pre-firing (atmospheric pressure, box furnace): Heat up to 80℃ at 0.3℃ / min and hold for 2h; heat up to 600℃ at 0.2℃ / min and hold for 1h; heat up to 1200℃ at 0.15℃ / min and hold for 2h; heat up to 1400℃ at 0.12℃ / min and hold for 2h; heat up to 1700℃ at 0.10℃ / min and hold for 4h; cool down to 1400℃ at 0.12℃ / min; cool down to 1200℃ at 0.20℃ / min and hold for 1h; cool down to 800℃ at 0.30℃ / min and hold for 1h, then cool down with the furnace. Billet placement method: 4 firing plates + 2 φ2mm-3mm alumina hollow spheres + alumina shrinkage plate + 2 hollow spheres, ensuring horizontal contact. Density after pre-firing: surface layer 2.8250 g / cm³, transition zone 2.8120 g / cm³, core 2.7950 g / cm³ (extremely low porosity).
[0071] HIP sintering: Heating: 5℃ / min to 800℃ and hold for 1h; 4℃ / min to 1100℃; 3℃ / min to 1300℃; 2℃ / min to 1500℃; 1℃ / min to 1640℃; Pressure: Pressurize to 180MPa before 1550℃ and hold for 4h (extend the holding time to completely eliminate residual porosity); Cooling: 1.5℃ / min to 1500℃; 2℃ / min to 1300℃; 2.5℃ / min to 1000℃; 3℃ / min to 400℃ and cool with the furnace; Atmosphere: ≥99.99%Ar.
[0072] (4) Annealing: air atmosphere, 1400℃ (increasing the annealing temperature enhances the decolorization effect), heating rate 2℃ / min, holding for 3h, cooling rate 2℃ / min.
[0073] Performance results: Appearance and integrity: The heat sink is flat and free from deformation, with no visible cracks or delamination.
[0074] Density: Overall density 2.87 g / cm³-2.88 g / cm³ (Archimedes method); Density uniformity: Surface layer 2.8781 g / cm³, transition layer 2.8765 g / cm³, core 2.8752 g / cm³, maximum density difference 0.10%.
[0075] Microstructure: SEM showed that pores were almost completely eliminated, grain boundaries were clear, and the average grain size was 6.5 μm (slightly larger but uniform, with no abnormal grains).
[0076] Thermal conductivity at room temperature: 285 W / (m·K) (laser flare method).
[0077] Flexural strength: 200MPa (still maintains a high level, meeting aerospace heat dissipation requirements).
[0078] Example 3: Preparation of a large BeO load-bearing insulating structural component (dimensions: 400×300×50mm) for a nuclear fusion device (1) Powder pretreatment: Beryllium oxide raw material powder (purity ≥99.5%, average particle size 300nm) was calcined and coarsened in a tunnel kiln at 1600℃, and the particle size after coarsening was about 800nm. Coarsened powder + 1.0wt.% magnesium trisilicate (enhancing grain boundary pinning) + 2.0wt.% PVA (improving green strength) + 2wt.% plasticizer DOP and glycerol + 1.8wt.% dispersant SD-00 + 1.0wt.% oleic acid + 2.5wt.% defoamer n-octanol, deionized water as medium, beryllium oxide milling balls, ball milling for 24 hours, slurry particle size D50≈1.2μm. Spray granulation: inlet temperature 230℃, outlet temperature 120℃, negative pressure in the tower about 200Pa, material pump pressure about 1.4MPa, the resulting granulated powder D50=120μm, angle of repose 30°. After sieving (40 / 60 / 80 / 100 mesh), the coarse and fine powders are graded in a 7:3 ratio.
[0079] (2) Vibration molding + vacuuming: The polyurethane mold (Shore A 90) was vibrated at a frequency of 80Hz and an amplitude of 0.5mm. Powder was filled while vibrating, and the vacuum was drawn to 0.06MPa and maintained for 12h.
[0080] Cold isostatic pressing: Stepwise pressurization (rate 1.0 MPa / s) to 160 MPa (holding pressure for 8 min, with each intermediate section holding pressure for 1 min); stepwise depressurization (rate 1.0 MPa / s, holding pressure for 30 s in each section), green body relative density 60%, maximum density difference 0.9%. Aging: 30℃, 70% humidity, stand for 18 h, then bake at 75℃ for 2 h at 10℃ increments.
[0081] (3) Sintering: Pre-firing (low temperature and slow speed to inhibit grain growth): Heat up to 80℃ at 0.5℃ / min and hold for 2h; heat up to 600℃ at 0.3℃ / min and hold for 1h; heat up to 1200℃ at 0.2℃ / min and hold for 2h; heat up to 1400℃ at 0.15℃ / min and hold for 2h; heat up to 1650℃ (lower limit of range) at 0.12℃ / min and hold for 4h; Cooling: 0.15℃ / min to 1400℃; 0.30℃ / min to 1200℃ and hold for 1h; 0.50℃ / min to 800℃ and hold for 1h, then cool with the furnace. Density after pre-firing: surface layer 2.7980g / cm³, transition zone 2.7850g / cm³, core 2.7701g / cm³ (openings are basically closed).
[0082] HIP sintering (low temperature and high pressure to avoid grain growth): Heating: 6℃ / min to 800℃ and hold for 1h; 4℃ / min to 1100℃; 3.5℃ / min to 1300℃; 2.5℃ / min to 1500℃; 2℃ / min to 1580℃; Pressure: pressurize to 160MPa before 1550℃ and hold for 2h (shorten the high temperature exposure time); Cooling: 2℃ / min to 1500℃; 2.5℃ / min to 1300℃; 3℃ / min to 1000℃; 4℃ / min to 400℃ and cool with the furnace; Atmosphere: ≥99.99%Ar.
[0083] (4) Annealing: air atmosphere, 1200℃, heating rate 4℃ / min, holding for 3h, cooling rate 4℃ / min.
[0084] Performance results: Appearance and integrity: Large structural components are free from cracks and warping, and have intact edges and corners.
[0085] Density: Overall density 2.856 g / cm³ 3 -2.86g / cm 3 Uniformity: Surface layer 2.8542 g / cm³ 3 Transition layer 2.8530 g / cm 3 The core has a density of 2.8523 g / cm³ and a maximum density difference of 0.07% (HIP achieves high uniformity despite low sintering temperature).
[0086] Microstructure: extremely fine grains, with an average grain size of 3.2 μm, clear grain boundaries, no pores, and no abnormal growth.
[0087] Room temperature thermal conductivity: 276 W / (m·K) (slightly lower than the previous two examples due to increased grain boundaries, but still much higher than conventional BeO).
[0088] Flexural strength: 210MPa (significantly improved, meeting high load-bearing requirements).
[0089] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing beryllium oxide ceramic structural parts, characterized in that, Includes the following steps, Step 1, Powder pretreatment: High-purity beryllium oxide powder is calcined and roughened, then sintering aid, binder and solvent are added and ball milled to obtain a slurry; the slurry is spray granulated to obtain granulated powder with an angle of repose ≤30°; Step 2, molding: After sieving the granulated powder obtained in Step 1, the powder is graded into coarse and fine particles, and then loaded into the mold by vibration filling. Vacuum is drawn to remove the gas between the powder particles, and then cold isostatic pressing is used to form a beryllium oxide ceramic green body. Finally, aging treatment is carried out to release stress. Step 3, Atmospheric pressure pre-sintering: The green blank obtained in step 2 is pre-sintered at a temperature not exceeding 1700℃. Step 4, hot isostatic pressing densification sintering and annealing: The sintered blank obtained in step 3 is subjected to hot isostatic pressing sintering in an inert gas atmosphere. The sintering temperature is not higher than the pre-sintering temperature in step 3. Then, it is annealed in an air atmosphere.
2. The method for preparing beryllium oxide ceramic structural components according to claim 1, characterized in that, The high-purity beryllium oxide powder mentioned in step one has a purity of ≥99.5% and an average particle size of 200nm-400nm; the calcination and coarsening are carried out in a tunnel kiln at a sintering temperature of 1500℃-1600℃, and the particle size of the coarsened powder is 700nm-800nm.
3. The method for preparing beryllium oxide ceramic structural components according to claim 1, characterized in that, The ball milling medium in step one is deionized water, the grinding balls are beryllium oxide balls, and the particle size D50 of the slurry after ball milling is 1μm-1.2μm.
4. The method for preparing beryllium oxide ceramic structural components according to claim 1, characterized in that, The sintering aid mentioned in step one is magnesium trisilicate; the binder is polyvinyl alcohol; the solvent also includes plasticizer, glycerol, defoamer, dispersant, and oleic acid; and the slurry has a solid content of 58%-62%.
5. The method for preparing beryllium oxide ceramic structural components according to claim 1, characterized in that, The sieving process in step two uses 40-mesh, 60-mesh, 80-mesh, and 100-mesh screens, with a fine powder gradation ratio of 20%-40%. The mold is a polyurethane mold with a Shore A hardness of 70-90.
6. The method for preparing beryllium oxide ceramic structural components according to claim 1, characterized in that, In step two, the vibration frequency of the vibratory powder filling is 20Hz-80Hz, the amplitude is 0.5mm-2mm, and the vibration continues during the powder filling process; the vacuum degree of the vacuuming is 0.04MPa-0.06MPa, and the vacuuming time is 6h-12h.
7. The method for preparing beryllium oxide ceramic structural components according to claim 1, characterized in that, The cold isostatic pressing process described in step two employs a stepped pressure increase and stepped pressure release method.
8. The method for preparing beryllium oxide ceramic structural components according to claim 1, characterized in that, The temperature regime for the segmented heating sintering described in step three is as follows: heating at 0.3℃ / min-0.5℃ / min to 80℃-100℃, and holding at that temperature for a period of time; Increase the temperature at a rate of 0.2℃ / min-0.3℃ / min to 600℃-800℃, and hold at that temperature for a period of time; Increase the temperature by 0.15℃ / min - 0.2℃ / min to 1100℃-1200℃, and hold for a period of time; Increase the temperature by 0.12℃ / min-0.15℃ / min to 1400℃-1500℃, and hold for a period of time; Increase the temperature by 0.1℃ / min-0.12℃ / min to 1650℃-1700℃, and hold for a period of time; Cooling: 0.1℃ / min-0.15℃ / min to 1300℃-1400℃, 0.15℃ / min-0.3℃ / min to 1100℃-1200℃ and hold for a period of time, 0.3℃ / min-0.5℃ / min to 600℃-800℃ and hold for a period of time before cooling down with the furnace.
9. The method for preparing beryllium oxide ceramic structural parts according to claim 1, characterized in that, The process parameters for hot isostatic pressing sintering in step four are as follows: heating rate 4℃ / min-6℃ / min to 600℃-800℃, holding at that temperature for a period of time, 3.5℃ / min-4℃ / min to 1000℃-1100℃, 3℃ / min-3.5℃ / min to 1300℃-1350℃, 2℃ / min-3℃ / min to 1400℃-1450℃, 1℃ / min-2℃ / min to 1550℃-1650℃, holding at that temperature and pressure for a period of time; The pressure is maintained at 150MPa-200MPa before reaching 1550℃ and held until the end of the heat preservation process; the cooling rate is 1℃ / min-2℃ / min to 1450℃-1500℃, 2℃ / min-2.5℃ / min to 1200℃-1300℃, 2.5℃ / min-3℃ / min to 800℃-1000℃, and 3℃ / min-4℃ / min to 300℃-400℃, after which the furnace is cooled. The introduced gas is Ar with a purity ≥ 99.99%; The annealing temperature in step four is 1200℃-1400℃, and the heating / cooling rate is 2℃ / min-4℃ / min.
10. The method for preparing beryllium oxide ceramic structural parts according to any one of claims 1-9, characterized in that, The pre-sintering arrangement method described in step three is as follows: Hollow spheres (2), shrinkage plates, hollow spheres (2), and beryllium oxide ceramic blanks are placed sequentially on the firing plate (4); the hollow spheres (2) are alumina spheres with a diameter of 2mm-3mm, and the shrinkage plates are alumina green blanks (3).